Virtual Assistants and Its Implementation in the Teaching-Learning Process - Cóndor-Herrera, Omar (2021)
Nowadays, technological advances encompass realities that in the last century were possible just as fantasies. Society lives now in a technological era where education must look for the path and tools to get the benefits that these advances offer, as well as the technological innate abilities that have been developed in students of this generation, who have been nominated as digital natives. For 2017 the capacities and use of virtual assistants have been significantly expanded, new products are offered in the market, although, these assistants are sub-used with basic functions solely, not taking into account the offered benefits. The present work aims to describe the different virtual assistants that could be used as an educational tool contributing to the teaching-learning process.